The ephemeral civilization : exploding the myth of social evolution - Snooks, G. D. (Graeme Donald) (Routledge, 1997)
The Ephemeral Civilization is an astonishing intellectual feat in which Graeme Snooks develops an original and ground-breaking analysis of changing sociopolitical forms over the past 3,000 years. Snooks challenges the prevailing theories of social evolutionism with an innovative approach which also looks ahead to the twenty-first century. The Ephemeral Civilization builds on the model of dynamic strategy outlined in the author's highly acclaimed companion volume, The Dynamic Society. The Ephemeral Society is divided into three parts - theory, history and.